Parametric analysis on the combustion and thermal performance of a swirl micro-combustor for micro thermophotovoltaic system. (1st May 2020) - Yang, Xiao; He, Zhihong; Cha, Suna; Zhao, Lei; Dong, Shikui; Tan, Heping
Abstract: A swirl micro-combustor which has strong capability to stabilize the flame has been developed and is promising to be used in micro thermophotovoltaic power generators in this work. Heat recirculation plays a requisite role in flame stability and thermal performance of micro combustors. Thus, the effects of three parameters (center inlet radius w 1, swirler width w 2, and step height w 3 ) that determine the size and location of the recirculation zones in a premixed hydrogen/air flame are investigated numerically. The results show that inner recirculation zone and corner recirculation zone generated by a swirler are critical for stabilizing the flame. The parameter w 1 has an insignificant influence on the thermal performance. Enlarging the inner recirculation zone by decreasing w 2 provokes enhanced heat transfer, and increases the temperature level and temperature non-uniformity of combustor walls. The size of corner recirculation zone is increased by increasing w 3, which raises the outer wall temperature uniformity. Based on the parametric analysis, the newly designed micro combustor possesses a high wall temperature level. Additionally, the energy output increment is between 9.1% and 14.2% at hydrogen mass flow rate of 0.0006 g/s when stoichiometric hydrogen/air ratio ranges from 0.6 to 1.4. Graphical abstract: Image 1025 Highlights: A novel swirl micro-combustor for micro TPV system is proposed. Geometrical parameters that determine the recirculation zones are studied. Inner and corner recirculation zones contributes to flame stabilization. Small swirler width improves wall temperature. Large step height increases wall temperature uniformity.